Sports Tourism Development Strategy for Physical Disabilities in Bengkulu City - Yahya Eko Nopiyanto; Ari Sutisyana; Fadli Dongoran (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to formulate a strategy for developing sports tourism for people with physical disabilities in Bengkulu City. The method used in this research was descriptive qualitative. The data analysis technique used SWOT analysis. The results of data analysis show that the results of IFAS and EFAS were used to determine the position of the quadrant. Strengths and weaknesses produce the X-axis, namely X = 1.93 – 1.71 = 0.21, and the Y-axis represents opportunities – threats, namely Y = 1.04 – 2.12 = -1.08 to produce quadrant II or strategy diversification. The strategy applied in this condition is the Strength-Threat, namely: 1) formulating a clear vision and mission to make the Pantai Panjang Tourism Location a friendly sports tourism location for physical disabilities, 2) equipping accessible facilities and infrastructure for physical disabilities at the Semarak Stadium and Youth Sports Center and increase promotion to the public about the achievements of athletes with physical disabilities, 3) involving the Youth and Sports Office, the Indonesian National Sports Committee, academics, private parties and sports clubs in fostering sports achievements, 4) involving the private sector for the development of facilities and infrastructure for physical disabilities, 5) involving the private sector to develop sports clubs for people with physical disabilities.